Effect of Chemical Hydrolysis on Degree of Hydrolysis and Functional Properties of Protein Hydrolysates Extracted from Leiognathus Equulus (Forsskål, 1775) - Marimuthu Manivannan; L. Vinothkumar; S. Devadharshini; G. Janarthanan; K.A. Martin Xavier; Vignaesh Dhanabalan (Journal of Indian Fisheries Association, 2020)
In the present study, two hydrolysis methods, acid and alkali were evaluated to produce fish protein hydrolysates (FPH) from 16.05±0.67% protein in wet-weight basis of silver belly fish (Leiognathus equulus). Acid hydrolysis was carried out by hydrochloric acid (pH 2) at 110 °C for 24 hrs. Alkali hydrolysis was performed by NaOH (pH 12.5) at 95 °C for 20 h. Results shown 8.60 to 16.90% degree of hydrolysis (DH) and 4.22 to 46.06% yield for acid hydrolysis. Alkali hydrolysis had shown 8.40 to 22.80 DH and6.66 to 59.51% yield. Acid hydrolysis exhibited higher emulsion properties (64.73±0.92%) at 1% concentration compared to acid. The foaming properties were obtained highest (69.00±1.41%) at 2% concentration in alkali hydrolysis.Thus the results revealed that alkali hydrolysis is a suitable and efficient as it rapidly hydrolysed the protein yielding higher DH and yield. Among the diﬀerent hydrolysates extracted, frame and mince hydrolysate showed better functional properties.